PERSEPSI KESESUAIAN PELATIHAN DENGAN PENINGKATAN KOMPETENSI DAN KINERJA ALUMNI PELATIHAN ABILITY TO EXECUTE (A2E) ESSENTIALS - Eddy Siswanto (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
This study is the result of a post-training evaluation of the Ability to Execute Essentials (A2E) course, which was held by BBPK Ciloto in 2024. The evaluation aims to describe alumni perceptions regarding the implementation, benefits, and self-improvement following the training. The Kirkpatrick evaluation model (results level) was used as the evaluative framework, while systems theory and the Health Belief Model (HBM) were applied to understand how participants’ perceptions were formed and influenced their performance in the work environment. A total of 42 alumni responded to the questionnaire, with 79% expressing a positive perception of the training’s impact on their performance. Topics such as effective communication, problem understanding, and prioritizing tasks were the competencies most frequently applied, while skills like generating new ideas, conducting pre-mortems, and coaching were less commonly implemented due to personal and contextual barriers. Respondents also felt that the A2E training did not fully address their specific performance needs, indicating a need for more advanced, practical, and application-based follow-up training. Supervisors’ and colleagues’ perceptions of the alumni generally support these findings, although the alignment of perceptions was not statistically significant. These evaluation results serve as a foundation for improving training design and developing more contextualized human resource strategies that directly impact organizational performance.